Aroma volatiles recovered in the water phase of cashew apple (Anacardium occidentale L.) juice during concentration - Sampaio, Karina L.; Garruti, Deborah S.; Franco, Bmaria Regina B.; Janzantti, Natalia S. [UNESP]; Da Silva, Maria Aparecida A. P. (Wiley-Blackwell, 2011)
BACKGROUND: There is a considerable loss of volatile compounds during the thermal concentration of cashew apple juice, damaging product quality, and as yet there is little research on the subject. Thus the purpose of this research was to identify the aroma volatiles evaporated off from cashew apple juice and recovered in the water phase during concentration of this beverage in an industrial plant. Water phase volatiles were extracted using dichloromethane, concentrated under a nitrogen flow, separated by gas chromatography (GC) and identified by GC-mass spectrometry. In order to determine the contribution of each volatile to the cashew aroma, five trained judges evaluated the GC effluents using the Osme GC-olfactometry technique.RESULTS: 71 volatiles were identified; of these, 47 were odour active. Alcohols were preferentially recovered in the cashew water phase, notably heptanol, trans-3-hexen-1-ol and 3-methyl-1-butanol, representing 42% of the total chromatogram area and imparting green grass and fruity aroma notes to the water phase. Esters represented 21% of the total chromatogram area, especially ethyl 2-hydroxyhexanoate, ethyl trans-2-butenoate and ethyl 2-methylbutanoate, and were responsible for the fruity/cashew-like aroma of the water phase. on the other hand, 3-methylbutanoic and 2-methylbutanoic acids were the volatiles that presented the greatest odour impact in the GC effluents of the water phase.CONCLUSION: Overall, the results of the present study strongly indicated that further concentration of the esters recovered in the water phase, either by partial distillation or by alternative technologies such as pervaporation, could generate a higher-quality natural cashew apple essence. (C) 2011 Society of Chemical Industry
Keywords: volatile compound; cashew apple; Anacardium occidentale; gas chromatography-mass spectrometry; aroma; water phase